1998
DOI: 10.1016/s0928-8244(98)00037-6
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor characterization of antigenic site A of foot-and-mouth disease virus presented in different vector systems

Abstract: The region 141-160 of the VP1 protein of foot-and-mouth disease virus known as site A is an immunodominant region that has been extensively studied for the purpose of developing a synthetic vaccine. In the present study, site A of foot-and-mouth disease virus was inserted in three different loops of the maltose-binding protein and its antigenicity was compared with site A presented as a conjugated synthetic peptide or inserted in beta-galactosidase. The affinity of antibodies elicited against the site A synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Potential applications of these sensor complexes include direct use of their maltose sensing capabilities in food production and processing (16), specifically in beer and bread production which utilize maltose as the primary sugar source and potentially other fermentative technology. Additionally, variants of this sensing scheme may be adapted for glucose monitoring of diabetic patients (8,25) or for sensing of surface glycoproteins of potential antigens (27).…”
Section: Discussionmentioning
confidence: 99%
“…Potential applications of these sensor complexes include direct use of their maltose sensing capabilities in food production and processing (16), specifically in beer and bread production which utilize maltose as the primary sugar source and potentially other fermentative technology. Additionally, variants of this sensing scheme may be adapted for glucose monitoring of diabetic patients (8,25) or for sensing of surface glycoproteins of potential antigens (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the serological diagnosis of infectious diseases, the use of allosteric biosensors, namely, hybrid enzymes that respond enzymatically to antibodies directed to foreign peptides displayed on the enzyme surface [216,217], is highly promising [218]. Multiple insertions of a major FMDV Bcell epitope from the VP1 capsid protein near the active site of recombinant β-galactosidases dramatically increased the enzyme responsiveness to specific antipeptide antibodies, including sera from infected animals [219,220]. It has been reported that recombinant β-galactosidases accommodating one or two different peptides from the FMDV NS protein 3B per enzyme monomer can be reactivated by anti-3B monoclonal antibodies (MAbs) and these recombinant βgalactosidases could be also efficiently reactivated by sera from infected animals that permitted differentiation between sera from infected animals and those from naïve and conventionally vaccinated pigs.…”
Section: Biosensors For Detection Of Fmdvmentioning
confidence: 99%